Investigations of bioresponsive polymers in triple negative breast cancers - Monteiro, Patricia (2019)
Triple negative breast cancer (TNBC) is a subtype of breast cancer which is defined by the lack of expression of standard molecular targets: estrogen and progesterone receptors and the lack of expression or amplification of human epidermal growth factor receptor 2. TNBC is characterised by aggressive progression, lack of standard therapies and poorer overall survival rates for patients. Existing targeted therapies are not applicable to this type of breast cancer; thus, conventional chemotherapy still remains the standard of care for the treatment of TNBC. The present work aims to develop functionalised biodegradable nanocarriers for the treatment of triple negative breast cancer using a novel triblock copolymer. Different strategies are used for the development of nanocarriers by taking advantage of endogenous specific stimulus or receptor expression in the triple negative breast cancer cells. In chapter 2, docetaxel (DTX)-loaded redox responsive crosslinked micelles are prepared using a novel biocompatible and biodegradable functionalised triblock copolymer mPEG-b-poly(D,L-lactide-co-α-N3-ε-caprolactone) for the treatment of TNBC. The empty micelles do not show any cytotoxicity in vitro in three cell lines tested i.e. MDA-MB-231 (triple-negative breast cancer), MCF7 (breast cancer) and MCF10A (breast epithelial cell line), whereas DTX-loaded reducible crosslinked micelles exhibit higher cytotoxicity against TNBC cells. Crosslinked and non-crosslinked micelles show high cellular uptake in MDA-MB-231 TNBC cells which is found to be concentration-dependent. The DTX-loaded crosslinked micelles induce higher levels of apoptosis, as assessed by the annexin V/PI assay and increase the caspase 3/7 activity in MDA-MB-231 cells in comparison to the cells treated with DTX-loaded un-crosslinked micelles and free DTX. Biodistribution results in healthy mice show that crosslinked micelles have increased stability in vivo in comparison to their non-crosslinked counterpart. Moreover, both formulations are found to be well tolerated and do not promote any adverse effect in vivo. In chapter 3, a triple negative breast cancer 3D cell culture model is developed for assessing the efficacy of docetaxel (DTX)-loaded crosslinked micelles against TNBC three-dimensional (3D) multicellular tumour spheroids. In addition, the ability of the redox responsive DTX-loaded crosslinked micelles to overcome the DTX resistance of the TNBC tumour spheroids is also investigated. The results of the efficacy assays show that DTX-loaded crosslinked micelles have the best efficacy against TNBC spheroids compared to control (un-crosslinked micelles) and free DTX. Moreover, the results indicate that 3D tumour spheroids exhibited higher innate resistance, especially to free docetaxel. In chapter 4, EGFR-targeted polymeric micelles using a peptide (GE11) that binds specifically to EGF receptor are prepared for synergistic co-delivery of docetaxel (DTX) and doxorubicin (DOX) aiming to treat triple negative breast cancer tumours. Results show that GE11-linked micelles at different peptide densities do not promote any toxicity in normal epithelial and breast cancer cell lines. However, the 15% GE11-linked micelles have a higher uptake in 2D monolayer and 3D spheroids of TNBC when compared to the 25% GE11-linked micelles and untargeted micelles. In addition, an advanced 3D co-culture system model of triple negative breast cancer with a non-tumorigenic cell line is also developed for the future assessment of the safety and efficacy of the formulations. Taken together, the results demonstrate that the designed functionalised micelles can be a promising and effective carrier system for future clinical applications to TNBC.